2011
DOI: 10.1039/c1cc11083g
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-induced CD response of oligonucleotide-conjugated metal nanoparticles

Abstract: Non-chiral metal nanoparticles conjugated with chiral oligonucleotide molecules demonstrated a circular dichroism (CD) at the plasmonic wavelengths due to aggregation effects.Metal nanoparticles (NPs) have raised much interest in recent years due to their unique optical and electronic properties. Functionalising their surface with biomolecules has led the way to applications in fields as various as biosensing, 1 drug delivery 2 and Surface Enhanced Raman Spectroscopy (SERS). 3The induction or enhancement of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 27 publications
(37 reference statements)
3
77
3
1
Order By: Relevance
“…First, adsorbed molecules may influence the electronic states of the metallic nanostructures. 20 Furthermore, molecular alignment at the substrate interface may play an important role, giving rise to aligned dipole–dipole interactions 21 or contributions to chiroptical phenomena through electric dipole–electric quadrupole coupling. 6 Finally, for large biomolecules which are of the same order as the spatial decay length of the inhomogeneous local electromagnetic fields, nonlocal effects may be important.…”
mentioning
confidence: 99%
“…First, adsorbed molecules may influence the electronic states of the metallic nanostructures. 20 Furthermore, molecular alignment at the substrate interface may play an important role, giving rise to aligned dipole–dipole interactions 21 or contributions to chiroptical phenomena through electric dipole–electric quadrupole coupling. 6 Finally, for large biomolecules which are of the same order as the spatial decay length of the inhomogeneous local electromagnetic fields, nonlocal effects may be important.…”
mentioning
confidence: 99%
“…For example, it was a powerful method to differentiate a secondary structure of proteins which can appear in the forms of α-helix, random coil, or β-sheet. Recently the concepts of chirality and CD have been brought to the field of plasmonics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . One of the motivations for this development is plasmon-enhanced sensing of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This is confirmed by the TEM images of NaDC modified Ag NPs containing dimers and linear chain assemblies (Figure 2c). It has been reported that the plasmonic CD signals can be enhanced in aggregates composed of chiral molecule-metal nanoparticle conjugates, which creates hot spots between Ag NPs and remarkably amplifies the electromagnetic fields [24]. The mechanism of plasmonic CD signals is based on the Coulomb interaction between chiral molecules and plasmonic modes in the hot spot.…”
Section: Resultsmentioning
confidence: 99%